Resistance to neonicotinoids is associated with metabolic detoxification mechanisms in Anopheles coluzzii from agricultural and urban sites in southern Benin - Tchigossou, G.; Dossou, C.; Tepa-Yotto, G.; Koto, M.; Atoyebi, S.M.; Tossou, E.; Adanzounon, D.; Gouété, M.; Sina, H.; Tchouakui, M.; Dione, Michel M.; Wondji, C.; et al. (Frontiers Media, 2024)
Background: Neonicotinoids are gradually being introduced into malaria vector control due to their mode of action that targets insect nicotinic acetylcholine receptors (nAChRs). However, prior to scaling up novel insecticides, it is important to assess the susceptibility of the mosquito population to this molecule. The present study aimed to determine the susceptibility level of mosquitos collected from agricultural and urban sites against neonicotinoids in Benin.